Actitud hacia el país de origen en productos de alto y bajo Involucramiento (2016)
The Country of Origin Effect (COO) has been studied in many studies over several years, and it has been a sseverate as a relevant factor to consider in the consumer behavior, due to it refers to consumers perception of a foreign product according to the label of country of origin . This paper responds to the differences in attitudes to expose the origin of Swis s watches and chocolates, products of high and low involvement respectively, in terms of cognitive, affective and conative attitudes. The results show that there is a significant difference in the attitude towards products of both types of involvement, but nevertheless, there is a variation on the attitude showed between men and wome